2013
DOI: 10.1371/journal.pone.0058979
|View full text |Cite|
|
Sign up to set email alerts
|

Platelets Recognize Brain-Specific Glycolipid Structures, Respond to Neurovascular Damage and Promote Neuroinflammation

Abstract: Platelets respond to vascular damage and contribute to inflammation, but their role in the neurodegenerative diseases is unknown. We found that the systemic administration of brain lipid rafts induced a massive platelet activation and degranulation resulting in a life-threatening anaphylactic-like response in mice. Platelets were engaged by the sialated glycosphingolipids (gangliosides) integrated in the rigid structures of astroglial and neuronal lipid rafts. The brain-abundant gangliosides GT1b and GQ1b were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 83 publications
7
98
0
2
Order By: Relevance
“…One of the commonly used rodent models to test the platelet functions in vivo is the tail bleeding test [22]. If the activation of platelets is inhibited, bleeding time increases as we described in our previous study [11]. Indeed we found that i.v.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…One of the commonly used rodent models to test the platelet functions in vivo is the tail bleeding test [22]. If the activation of platelets is inhibited, bleeding time increases as we described in our previous study [11]. Indeed we found that i.v.…”
Section: Resultssupporting
confidence: 63%
“…It was also demonstrated that GA may cause specific symptoms such as chest pain, flushing, dyspnea, and anxiety [24]. As we demonstrated previously in mouse model, dyspnea and restless behavior are both associated with massive platelet activation/degranulation and associated with the release of potent mediators from platelets such as histamine [11]. Other investigators found that in humans massive platelet activation/degranulatuion is caused by the administration of radiographic contrast media into blood vessels, indicating that human platelets may degranulate in response to the injection of chemical substances [25].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…These data already suggested an immune mediated role for platelet contribution in MS, but were then largely forgotten in future generations of MS researchers. Indeed, current studies suggest that platelet depletion reduces disease severity and inflammation in mice that were subjected to experimental autoimmune encephalomyelitis (EAE), a classical animal model of CNS inflammation to study the pathogenesis of MS [30,31,32]. In particular, a number of studies have demonstrated that platelets are present along with an increased activation status in the peripheral blood and in plaques of MS patients as indicated by elevated PMP levels, P-selectin expression (also known as CD62P), increased levels of platelet-activating factor (PAF) and upregulation of GpIIb receptor (see Figure 1) [30,33,34,35,36].…”
Section: Role Of Platelet-driven Neuroinflammation In Multiple Sclmentioning
confidence: 99%